Introvert Self Disclosure and Al-Haya in Islamic Perspective: Study of Takhrij and Syarah Hadith - Andaryani, Fitri; Fitriani, Fitriani (Journal of Takhrij Al-Hadith, 2022)
This study aims to discuss the hadith about shame. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about shame in Bukhari No. 8. The results and discussion of this study indicate that the status of authentic quality hadith fulfills the qualifications of maqbul ma’mul bih for Islamic practice. This study concludes that the hadith narrated by Bukhari No. 8 is relevant to be used as motivation and a good role model in maintaining shame.